The Effect of Customer Relationship Management on Customer Loyalty (A Case Study on Swiss-Belinn Malang) - Deasy Chrisnia Natalia; Rugeri Fadhlihalim (Journal of Indonesian Tourism and Development Studies, 2022)
Competition in the hotel industry in the 4.0 era is getting tighter. The hospitality business is run offline and online, both for marketing and communication with customers, with a wide selection of digital platforms. Hotel industry participants must be able to adapt to new competitors who use technology to serve customers. If not, the hotel business that is run will not be able to compete. To survive and compete, companies must begin to focus on providing value to customers (customer value) that attracts buyers and must be well understood by the seller. Efforts should also be made to increase customer loyalty. Customers have various reasons for carrying out a purchase decision. Before choosing to stay at a particular hotel, there are various considerations. The key to the success of a company in retaining customers is to have a good relationship with the customer themself. The research objectives are a. To determine the effect of Customer Relationship Management (CRM) on Customer Loyalty in Swiss-Bellin Malang b. To find out how much influence CRM has on Customer Loyalty at Swiss-Bellin Malang. The research method used in this research is descriptive quantitative. This research was carried out by distributing questionnaires to people in Malang City who had stayed at the Swiss-Bellin Malang with simple random sampling. Testing and data processing used SPSS version 25 with simple linear regression. The result showed that CRM, which consisted of continuity marketing, one-to-one marketing, and partnering program, affects customer loyalty at Swiss-Bellin Malang.Keywords: Customer loyalty, Customer Relationship Management.